Peran Ario Damar dalam Masuknya Islam di Sumatera Selatan: Kajian Sejarah Makamnya - Aqilah Fakhriyari Auliya; Sofiia Muntazza; Herni Mandala Putri; Hudaidah Hudaidah; Risa Marta Yati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The tomb of Ario Damar in Palembang City represents one of the important historical sites for understanding the political, social, and religious dynamics during the transitional period from the influence of the Majapahit Kingdom to the development of Islam in the South Sumatra region. The study of this site employs the historical method through the stages of heuristics, source criticism, interpretation, and historiography, using a qualitative approach. Data were collected through direct observation of the Ario Damar tomb complex and literature studies derived from scientific journals, academic articles, and relevant historiographical works. The analysis indicates that the existence of the Ario Damar tomb not only represents a physical relic of a prominent figure within the governmental structure of Palembang in the fifteenth century but also serves as material evidence reflecting the process of cultural and religious transformation in the region. The tomb site demonstrates historical connections between the political authority of Majapahit, the early development of Islam in Palembang, and the political and cultural relations between Java and Sumatra. In addition to its historical significance, the Ario Damar tomb also holds social and cultural functions as a space of collective memory for the community, which continues to be used as a site of pilgrimage and historical reflection. Therefore, the preservation of the Ario Damar tomb site is essential to maintain cultural heritage while strengthening its role as a source of local historical learning and the development of sustainable historical tourism.